The Effect of Profitability, Leverage, Liquidity and Sharia Supervisory Board on Disclosure of Islamic Social Reporting - Eko Wahyudi; Imelda Dian Rahmawati (Indonesian Journal of Islamic Studies, 2022)
This study aims to determine the Effect of Profitability, Leverage, Liquidity and Sharia Supervisory Board on Disclosure of Islamic Social Reporting (Study on Islamic Banking Companies Listed on the Indonesia Stock Exchange 2016-2019 Period). The sampling method used is purposive sampling method. The number of companies that were sampled in this study were 10 Islamic Banking Companies Listed on the IDX for the 2016-2019 period. The data used is secondary data. The data analysis method used in this research is Multiple Linear Regression. The results of this study indicate that Profitability Affects Disclosure of Islamic Social Reporting in Islamic Banking Companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2019 period. Leverage Affects Disclosure of Islamic Social Reporting in Islamic Banking Companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2019 period. Liquidity Affects Disclosure of Islamic Social Reporting in Islamic Banking Companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2019 period. Sharia Supervisory Board Influences on Disclosure of Islamic Social Reporting in Sharia Banking Companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2019 period.